Internet of Things Security: Firmware Approach - Đinh Công Đoan (Journal of Technical Education Science, 2024)
Internet of Things (IoT) is increasingly widely used, creating many opportunities to bring people smart applications (smart city, smart home, smart health, etc.), making our life more convenient, higher production efficiency (smart industry, smart agriculture). Besides the advantages, many security challenges also arise such as privacy issues, authentication, management issues, information storage, etc. The different factors make the issue of security in the IoT environments more challenging than that of the regular information technology (IT) devices. The IoT environment gives rise to problems and vulnerabilities, the IoT applications create various cyber threats. There have been various security and privacy attacks on devices that have been deployed: the Mirai attack in 2016 was estimated to have infected about 2.5 million Internet-connected devices and launched the Distributed denial of service (DDOS) attack. The IoT devices are also implanted into the human body to monitor the vital status of various organs. These devices are targets for attacks to falsify data. Such attacks, if any, will very dangerous. This article focuses on presenting the challenges of securing the IoT systems, then diving into a security aspect of the IoT systems coming from inside the hardware device - the firmware of the device.